Progressive Multifocal Leukoencephalopathy: Current Insights - Marge Kartau; Jussi OT Sipilä; Eeva Auvinen; Maarit Palomäki; Auli Verkkoniemi-Ahola (Dove Press Ltd, 2022)
Cases of PML should be evaluated according to predisposing factors, as these subgroups differ by incidence rate, clinical course, and prognosis. The three most significant groups at risk of PML are patients with hematological malignancies mostly previously treated with immunotherapies but also untreated, patients with HIV infection, and patients using monoclonal antibody (mAb) treatments. Epidemiological data is scarce and partly conflicting, but the distribution of the subgroups appears to have changed. While there is no specific anti-JCPyV treatment, restoration of the immune function is the most effective approach to PML treatment. Research is warranted to determine whether immune checkpoint inhibitors could benefit certain PML subgroups. There are no systematic national or international records of PML diagnoses or a risk stratification algorithm, except for MS patients receiving natalizumab (NTZ). These are needed to improve PML risk assessment and to tailor better prevention strategies.